Advancements in cosmogenic 38Ar exposure dating of terrestrial rocks - Oostingh, K.; Jourdan, Fred; Danisik, Martin; Evans, Noreen (Pergamon, 2017)
© 2017 Elsevier Ltd Cosmogenic exposure dating of Ca-rich minerals using 38 Ar on terrestrial rocks could be a valuable new dating tool to determine timescales of geological surface processes on Earth. Here, we show that advancement in analytical precision, using the new generation multi-collector ARGUSVI mass spectrometer on irradiated pyroxene and apatite samples, allows determination of cosmogenic 38 Ar abundances above background values, as well as discrimination of 38 Ar/ 36 Ar ratios (1s absolute precision of ±0.3%) from the non-cosmogenic background value. Four statistically significant cosmochron ( 38 Ar/ 36 Ar vs 37 Ar/ 36 Ar) diagrams could be constructed for southeast Australian pyroxene samples from the Mt Elephant scoria cone for which a combined apparent exposure age of 313 ± 179 ka (2s) was obtained when using a 38 Ar production rate (Ca) of 250 atoms /g Ca/ yr. This exposure age overlaps within error with the known 40 Ar/ 39 Ar eruption age of 184 ± 15 ka (2s). Although apatite shows much larger 38 Ar abundances than pyroxene, our modelling and analyses of unirradiated apatite suggest that apatite suffers from both natural and reactor-derived chlorogenic as well as natural nucleogenic contributions of 38 Ar. Hence, we suggest that cosmogenic 38 Ar exposure dating on irradiated Ca-rich (and eventually K-rich), but Cl-free, terrestrial minerals is a potential valuable and accessible tool to determine geological surface processes on timescales of a few Ma. Calculations show that with the new generation multi-collector mass spectrometers an analytical uncertainty better than 5% (2s) can be achieved on samples with expected exposure ages of > 4 Ma.